Development of RR soybean in function of glyphosate doses and Bradyrhizobium inoculation - Bossolani, Joao W. [UNESP]; Poloni, Nadia M. [UNESP]; Lazarini, Edson [UNESP]; Bettiol, Joao V. T. [UNESP]; Fischer Filho, Joao A. [UNESP]; Negrisoli, Matheus M. [UNESP] (Univ Federal Campina Grande, 2018)
Soybean has traditionally been produced in systems that include the use of herbicides, often in higher than recommended doses. The process of symbiotic nitrogen fixation in legumes can be hampered by these herbicides, both by direct effects on rhizobia and indirect effects on the host plant. An outdoor experiment was performed to evaluate the effects of different doses of a glyphosate herbicide on Bradyrhizobium strains and biological nitrogen fixation in soybean BMX Potencia RR plants. Soybean seeds were inoculated with Bradyrhizobium elkanii (SEMIA 5019) and Bradyrhizobium japonicum (SEMIA 5079) strains in a commercial liquid inoculant. The treatments consisted of the absence and presence of Bradyrhizobium genotypes inoculated via seed and four doses of the herbicide glyphosate applied on the leaves (0, 1.0, 2.0, and 4.0 L ha(-1) of the commercial product) at the V (3) stage. The leaf chlorophyll index of inoculated RR soybean plants did not change on the application of glyphosate and, regardless of inoculation, plants had the capacity to recover from the effects of glyphosate application, without impaired development.
Keywords: Bradyrhizobium sp.; Glycine max (L.) Merril; herbicide